EFEKTIFITAS BIMBINGAN KELOMPOK DENGAN TEKNIK SELF MANAGEMENT TERHADAP DISIPLIN BELAJAR SISWA - Navira Desy; Tiara Fani; Abdul Muhid (Educouns Journal: Jurnal Pendidikan dan Bimbingan Konseling, 2022)
This research is motivated by the behavior of students who are less disciplined in obeying school rules, doing assignments. This study was made with the aim of knowing the effectiveness of group guidance services using self-management techniques to improve student learning discipline. The thing that will change from this group guidance service with self-management technique is the attitude of learning discipline and low responsibility. This research method is a qualitative method with a literature review approach by using theoretical studies from various sources. The result of this study are group guidance services using effective self-management techniques to improve student learning discipline.